2015
DOI: 10.1021/jacs.5b01968
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metagenomics: Finding Rare Tryptophan Dimer Natural Products in the Environment

Abstract: Natural product discovery from environmental genomes (metagenomics) has largely been limited to the screening of existing environmental DNA (eDNA) libraries. Here, we have coupled a chemical-biogeographic survey of chromopyrrolic acid synthase (CPAS) gene diversity with targeted eDNA library production to more efficiently access rare tryptophan dimer (TD) biosynthetic gene clusters. A combination of traditional and synthetic biology-based heterologous expression efforts using eDNA-derived gene clusters led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 48 publications
(112 reference statements)
1
42
0
Order By: Relevance
“…One of the ultimate goals of studying NP biosynthetic diversity is to guide the identification of new bioactive metabolites. One way NPST data can assist with this is by identifying environments that are rich in gene cluster families that are known to encode clinically important metabolites (29)(30)(31)(32)(33)(34)(35). Biosynthetic gene clusters that encode families of structurally related metabolites generally share a common evolutionary ancestor and therefore exhibit high sequence identity.…”
Section: Resultsmentioning
confidence: 99%
“…One of the ultimate goals of studying NP biosynthetic diversity is to guide the identification of new bioactive metabolites. One way NPST data can assist with this is by identifying environments that are rich in gene cluster families that are known to encode clinically important metabolites (29)(30)(31)(32)(33)(34)(35). Biosynthetic gene clusters that encode families of structurally related metabolites generally share a common evolutionary ancestor and therefore exhibit high sequence identity.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown eSNaPD classification to be a robust indicator of a functional relationship between a microbiome-derived gene cluster yielding an AD or KS domain sequence tag and a curated known gene cluster (20)(21)(22). Based on empirical data from previous metagenomic analyses (20)(21)(22)(23), the homology cutoffs used in this study (e value < 10 −100 ) will identify gene clusters with a high likelihood of encoding either the same metabolite or a novel derivative (congener) of the metabolite encoded by the matching curated gene cluster.…”
Section: Resultsmentioning
confidence: 99%
“…AD and KS amplicons were assigned to known biosynthetic gene clusters using the eSNaPD program (18,19). Empirical exploration with the eSNaPD algorithm has shown that e values as high as 10 −40 to −60 return reliable gene cluster predictions (20)(21)(22). We used an expectation value to 10 −100 for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Screening is especially challenging for large complex metagenomes such as soil, which can contain up to 10 5 unique species and require multimillion-membered mega-libraries for sufficient coverage [87, 88]. Conventional function- and sequence-based methods involve screening libraries for easily observable phenotypes or the presence of target DNA sequences, respectively (Figure 2a).…”
Section: Metagenomics-driven Drug Discoverymentioning
confidence: 99%
“…New chemical functionalities can also be discovered using this method. A new subclass of natural tryptophan dimers possessing a pyrrolinium indolocarbazole core was uncovered by focusing on eDNA-derived gene clusters with sequence tags that are not closely associated with characterized tryptophan dimer BGCs [88]. In general, while targeted metagenome mining may not be suitable for the discovery of fundamentally distinct chemical entities, it can be used to survey the biosynthetic potential of environmental samples as well as identify and recover novel variants of pharmaceutically relevant BGCs for downstream analyses (Figure 2b).…”
Section: Metagenomics-driven Drug Discoverymentioning
confidence: 99%